ChemInform Abstract: Use of 1‐Pentafluorosulfanyl‐phenylacetylenes for the Preparation of SF5‐Substituted Five‐Membered Ring Heterocycles Through 1, 3‐Dipolar Cycloadditions. Isoxazoles and Isoxazolines. Issue 47 (November 2015) - Lopez, Simon E.; Mitani, Akira; Pena, Priscila; Ghiviriga, Ion; Dolbier, William R. Jr.
Abstract: 1, 3‐Dipolar cycloaddition reactions of SF5 ‐substituted arylacetylenes with nitrile oxides generated in situ from (IV) or with nitrones (VI) affords isoxazole or isoxazoline derivatives of type (V) or (VII).